The Effect of "Cipit Bar" Poetry Learning Model on Poetry Writing Ability and Poetry Appreciation of Elementary School Students - Asriani, Nur; Azis, Sitti Aida; Arief, Tarman Andi (Pedagogik Journal of Islamic Elementary School, 2023)
This study aims to analyze the effect of using the Cipit Baru Poetry Learning Model on the reading comprehension ability and reading interest of fourth grade elementary school students. A quasi-experimental design with a post test only-non-equivalent control group focus was applied to all fourth grade students (total sampling). Research data were collected through poetry writing ability tests and poetry appreciation with two assessment rubrics. The results showed that there was a partial and simultaneous effect of the use of the "CIPIT BARU" Poetry Learning Model on the ability to write poetry and appreciate poetry in grade IV elementary school students at both research loci. The conclusion of this study is that the use of the "CIPIT BARU" Poetry Learning Model can improve the ability to write poetry and appreciate poetry in grade IV elementary school students, as well as the importance of applying an innovative poetry learning approach in increasing students' reading interest and comprehension.